Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1093/carcin/bgs256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and alterations of genes involved in NFκB/TNFAIP3- and NLRP3-inflammasome signaling affect susceptibility and outcome of colorectal cancer

Abstract: Colorectal tumors are continuously exposed to an inflammatory environment, which together with mitogenic signals sustain several cancer hallmarks. Nuclear factor-kappa B (NFκB) is a major regulator of inflammation and variation in NFκB-associated genes could potentially be used as biomarkers to identify patients with increased risk of colorectal cancer (CRC) development, and/or a rapidly progressing disease. In this study, 348 CRC cases and 806 randomly selected healthy individuals from southeastern Sweden wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…103 Mechanistically, TNFAIP3 inhibits nuclear factor-κB signaling by controlling the ubiquitination of proteins related to nuclear factor-κB that is involved in tumorigenesis. It has been established that the composition of gut microbes may associate with the risk for CRC, and thus whether TNFAIP3 is involved in host responses to gut microbiota deserves further investigation.…”
Section: Chr6mentioning
confidence: 99%
“…103 Mechanistically, TNFAIP3 inhibits nuclear factor-κB signaling by controlling the ubiquitination of proteins related to nuclear factor-κB that is involved in tumorigenesis. It has been established that the composition of gut microbes may associate with the risk for CRC, and thus whether TNFAIP3 is involved in host responses to gut microbiota deserves further investigation.…”
Section: Chr6mentioning
confidence: 99%
“…Several studies demonstrate the role of NLR inflammasomes in cancer. For example, NLRP3 gene polymorphisms have been associated with melanoma [16], myeloma [17], and colorectal cancer [18]. In the present study we characterized NLR genes in urine sediments and evaluated their contribution to predict bladder cancer together with CK20.…”
Section: Introductionmentioning
confidence: 95%
“…(Naugler and Karin 2008;Sarkar and Li 2008;Ungerback et al 2012). Many studies found that NF-κB is overexpressed in a variety of cancer, including cervical cancer (Barkett and Gilmore 1999;Gilmore et al 2002;Luque and Gelinas 1997;Rayet and Gelinas 1999).…”
Section: Introductionmentioning
confidence: 99%